New β-Cyclodextrin Entrapped in Polyethyleneimine Film-Modified Electrodes for Pharmaceutical Compounds Determination - Luminţa Fritea; Mihaela Tertiş; Cecilia Cristea; Robert Săndulescu (Sensors, 2013)
The electrochemical behavior of ascorbic acid and uric acid on glassy carbon bare electrodes and ones modified with β-cyclodextrin entrapped in polyethyleneimine film has been investigated using square wave voltammetry. The electrode modification was achieved in order to separate the voltammetric peaks of ascorbic acid and uric acid when present in the same solution. On the modified electrodes the potential of the oxidation peak of the ascorbic acid was shifted to more negative values by over 0.3 V, while in the case of uric acid, the negative potential shift was about 0.15 V compared to the bare glassy carbon electrode. When the two compounds were found together in the solution, on the bare electrode only a single broad signal was observed, while on the modified electrode the peak potentials of these two compounds were separated by 0.4 V. When the uric acid concentration remained constant, the peak intensity of the ascorbic acid is increased linearly with the concentration (r2 = 0.996) and when the ascorbic acid concentration remains constant, the peak intensity of the uric acid increased linearly with the concentration (r2 = 0.992). FTIR measurements supported the formation of inclusion complexes. In order to characterize the modification of the electrodes microscopic studies were performed. The modified electrodes were successfully employed for the determination of ascorbic acid in pharmaceutical formulations with a detection limit of 0.22 µM.